2017
DOI: 10.1007/s00464-017-5591-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous conversion of gastric band to sleeve gastrectomy is associated with increased postoperative complications: an analysis of the American College of Surgeons National Surgical Quality Improvement Program

Abstract: Serious morbidity following LSG is uncommon; however, CONV is associated with a modest increase in risk-adjusted adverse 30-day outcomes. Patients being evaluated for CONV should be counseled about the added risks versus LSG alone. Further research is warranted to identify whether the incremental risks of CONV may be modifiable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Thus, some series that evaluated SG as a rescue of failing GB have been published. Most of these series described logically an increased rate in complications in cases of secondary SG [6,14] . In their analysis of the American College of Surgeons National Surgical Quality Improvement Program database, Dietch et al [6] showed that conversion of GB to SG compared to primary SG was associated with increased odds of serious 30-day morbidity (odd ratio of 1.44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, some series that evaluated SG as a rescue of failing GB have been published. Most of these series described logically an increased rate in complications in cases of secondary SG [6,14] . In their analysis of the American College of Surgeons National Surgical Quality Improvement Program database, Dietch et al [6] showed that conversion of GB to SG compared to primary SG was associated with increased odds of serious 30-day morbidity (odd ratio of 1.44).…”
Section: Discussionmentioning
confidence: 99%
“…Mean preoperative BMI at the time of GB implementation was 46.7 kg/m 2 (35.0 -64.0). After GB implementation, the maximum weight loss achieved was at a mean time interval of 5 months (3)(4)(5)(6)(7)(8)(9)(10)(11)(12), representing a mean minimum BMI of 31.7 kg/m 2 (21 -46.3) and a mean EWL of 54.1% (0 -127).…”
Section: Population Studymentioning
confidence: 99%
“…However, the evidence in the literature regarding the effectiveness of OS-SG and TS-SG after failed AGB is inconsistent (15,(22)(23)(24). Due to the lack of evidence and the heterogeneous number of patients included in some clinical trials, there are still no clear guidelines for conversion from AGB to SG at One-Step or Two-Step (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Since SG and RYGB are adequate procedures in Germany, switching from AGB to SG or RYGB is an exciting option for revision operations [31,32,33]. However, there are still no clear guidelines for conversion from AGB to RYGB and SG [34,35,36] and statements in the literature vary regarding the effectiveness of both surgical procedures [37,38,39]. Chansaenroj et al [40] analyzed data from 275 patients after revision surgery of a failed AGB.…”
Section: Discussionmentioning
confidence: 99%